Online Community Marketing Strategies for Building Customer Loyalty at UD. Surya in Gunungsitoli City - Gulo, Destin; Bate'e, Maria Magdalena (Amkop Management Accounting Review (AMAR), 2025)
This research entitled "Online Community Marketing Strategies for Building Customer Loyalty at UD. Surya in Gunungsitoli City" aims to examine the implementation of online community-based marketing strategies by UD. Surya and evaluate effective online community characteristics supporting these strategies. The study also identifies applied online marketing strategies, understands online community interaction roles in customer loyalty formation, and analyzes how online community strategies contribute more significantly than conventional marketing approaches. The research employs qualitative methodology with data collection through in-depth interviews with business owners, marketing staff, and UD. Surya community members. Results show UD. Surya implements online community-based marketing through WhatsApp Groups and Facebook, functioning as direct communication channels. Effective online communities are characterized by active member engagement, open two-way communication, and added value including product information, special discounts, and rapid business responses. Online marketing strategies encompass digital product promotion, brand strengthening through engaging content, and customer testimonials for trust-building. Online community interactions prove crucial in creating belonging and customer loyalty toward UD. Surya. Compared to conventional strategies, online community approaches are more efficient, interactive, and directly impact loyalty and customer growth, making online communities relevant and effective marketing strategies supporting UMKM business growth in the digital era.